Identifying Key Factors for Burnout Among Orthopedic Surgeons Using the Analytic Hierarchy Process Method - Shiqian Wang; Lin Li; Yanjun Jin; Rui Liao; Yen-Ching Chuang; Yen-Ching Chuang; Yen-Ching Chuang; Zhong Zhu (Frontiers Media S.A., 2023)
Objectives: To develop an evaluation model for, and identify key factors contributing to, burnout in orthopedic surgeons, providing a reference for the management of burnout among orthopedic surgeons in hospitals.Methods: We developed an analytic hierarchy process (AHP) model with 3 dimensions and 10 sub-criteria based on an extensive literature review and expert assessment. We used expert and purposive sampling and 17 orthopedic surgeons were selected as research subjects. The AHP process was then used to obtain the weights and to prioritize the dimensions and criteria for burnout in orthopedic surgeons.Results: The dimension of C1 (personal/family) was the key factor affecting burnout in orthopedic surgeons, and in the sub-criteria, the top four sub-criteria were C11 (little time for family), C31 (anxiety about clinical competence), C12 (work-family conflict), and C22 (heavy work load).Conclusion: This model was effective in analyzing the key factors contributing to job burnout risk, and the results can inform improved management of the levels of burnout affecting orthopedic surgeons in hospitals.